2023
DOI: 10.1177/17298806231168486
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influence of the baby schema effect on the cuteness and trustworthiness of social robot faces

Abstract: Exploring people’s attitudes toward the appearance design of social robots in a low-cost and efficient way, and enhancing the experience of human–robot interaction have always been topics of concern for robot developers and interaction designers. This study aimed to explore the influence of the baby schema effect on users’ perceptions of cuteness and trustworthiness pertinent to social robot faces through two experiments. Experiment 1 used 100 uniformly processed pictures of robot faces in the real world to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The baby schema refers to the infantile appearance that babies and children have, including large eyes and a round face, traits that Pepper exhibits. The baby schema is known to induce an attentional bias in a human context (Brosch et al, 2007), and has already been shown to relate to an increase in trustworthiness in robots (Chen & Jia, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The baby schema refers to the infantile appearance that babies and children have, including large eyes and a round face, traits that Pepper exhibits. The baby schema is known to induce an attentional bias in a human context (Brosch et al, 2007), and has already been shown to relate to an increase in trustworthiness in robots (Chen & Jia, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cute objects influence people’s compliance behaviors (Bellfield et al ., 2011), task attention (Nittono et al ., 2012), indulgent consumption (Nenkov and Scott, 2014), recycling behaviors (Wang et al ., 2017), decisions relating to temporal focus (Li et al ., 2019), risk preferences (Li and Yan, 2021), brand attitude (Septianto and Paramita, 2021), brand engagement (Lee and Hsieh, 2019), responses to destination marketing (Su and Li, 2023; Ye et al ., 2023; Xu et al ., 2022), prosocial behavior (Yang et al ., 2022; Jang, 2022; Shin and Mattila, 2021) and reaction after brand transgressions (Septianto and Kwon, 2022). Recent research has found an impact of cuteness in new domains, including AI (Lv et al ., 2022), AI voice assistants (Yu et al ., 2022), social robot faces (Chen and Jia, 2023) and insect-based foods (Marquis et al ., 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This effect of infantile features on human cuteness perception is generalized to non-human animal faces [ 30 , 31 ] and even artificial objects such as cars [ 32 ], which attracts attention from applied fields of research such as product design (e.g. [ 33 ]). It may seem, therefore, that the baby schema hypothesis has been established on a solid body of empirical research.…”
Section: Introductionmentioning
confidence: 99%